The The Impact of COVID-19 on Immunization Services - Mathema, Smriti (Journal of Lumbini Medical College, 2020)
There was a time when epidemics were of interest only to historians. In spite of the knowledge of the risks of emergent infectious diseases, Coronavirus disease of 2019 (COVID-19) managed to disrupt the entire world. This new virus has the capacity to evade, adapt, diversify and persist. Human factors such as global travel, human-animal contact, urban crowding and ecological changes have helped favor the rapid spread. Epidemics are known to eventually resolve, whether succumbing to societal action or having exhausted the supply of susceptible victims. COVID-19 too will be contained but it will leave a trail of devastating health consequences for low- and middle-income countries (LMIC) including Nepal. When governments responded in the hopes of slowing the course of the pandemic and reducing the total mortality, stringent controls were implemented, including school closures, bans on public gatherings, and other forms of isolation or quarantine. In Nepal, a nationwide complete lockdown commenced on the 24th March, 2020. This brought about a drastic decrease in demand for hospital services, mainly due to inaccessibility or the health care seekers’ apprehension of contracting the virus during a hospital visit. Elective surgeries and procedures were temporarily discontinued and preventive care such as antenatal and well-baby visits came to a complete halt in majority of the institutions nationwide. Although mortality rates for COVID-19 appeared to be low in children and in women in the reproductive age, these groups might be disproportionately affected by the disruption of routine health services, particularly in LMICs.